Long-term effectiveness of BioEnterics intragastric balloon in obese patients - Yüksel Gümürdülü,; Ümit Bilge Doğan,; Mustafa Salih Akın,; Burçak Evren TAŞDOGAN,; Serkan YALAKİ, (Turkish Journal of Gastroenterology, 2019)
-